413 Inpatient Sleep Screens: Effective for Screening but Poor Follow Up. (3rd May 2021) - Chawla, Upneet; Chadha, Avneet; Martin, Abigail; Culnan, Elizabeth; Kirkpatrick, Aaron; Arantes, Henry; Lastra, Alejandra
Abstract: Introduction: Only 20% of adult Americans with Obstructive Sleep Apnea (OSA) are thought to have been diagnosed. Portable monitors (PM) can provide shorter time to diagnosis and treatment in at risk populations including inpatients. Data on inpatient sleep screen testing outcomes and population phenotypes are limited. We hypothesized that inpatients undergoing sleep screens via PM have higher disease severity but are less adherent to follow up. Methods: We conducted a retrospective observational study comparing severity of OSA based on apnea-hypopnea index (AHI) and compliance with follow up between patients who received inpatient vs. outpatient sleep screens. There was a total of 347 patients, 18 years and older, who received a sleep screen from August 2017 to August 2018. Exclusion criteria were cancellations/no shows (13.56% inpatients vs. 13.51% outpatients) or loss of data (26.12% inpatients vs. 23.72% outpatients). For analysis, t-test and chi-square were used for continuous and categorical variables respectively. Results: The patients diagnosed with severe OSA were more than double in the inpatient group vs. the outpatient group, 46.7% and 21.7% respectively. The inpatient group had a higher average AHI (30/h) compared to the outpatient group (20.3/h). 30.7% of the inpatient group were adherent with their follow up vs. 83.3% of the outpatient group. A chi-square test of independence demonstrated a significant difference between testing location and follow up (p < .001). Those in the inpatient group were significantly older (mean 60.4 years old) than the outpatient group (47.5 years old). There was no significant difference in gender between the groups. The inpatient group had significantly higher average body mass index (39.9 kg/m2) when compared to the outpatient group (34.3 kg/m2). Conclusion: Hospitalized patients screened for OSA with portable monitors are significantly more likely to have severe disease when compared to outpatients. Despite this, adherence to follow up is poor. Systematic evaluation of inpatient OSA screening program effectiveness and factors impacting adherence to follow up and treatment are needed. Support (if any):